Surface Reaction Kinetics of the Oxidation and Reforming of CH4 over Rh/Al2O3 Catalysts. Issue 3 (25th January 2016) - Karakaya, Canan; Maier, Lubow; Deutschmann, Olaf
ABSTRACT: An 48‐step sur face reaction mechanism with thermodynamic consistent kinetic data is presented for the catalytic conversion of the gaseous chemical system H2 /O2 /H2 O/CO/CO2 /CH4 over Rh/Al2 O3 catalysts. Total and partial oxidation as well as steam reforming and dry reforming of methane over Rh catalysts is studied experimentally and numerically at varying temperature and composition. The results are used to extend the kinetic schemes we developed for H2 oxidation, CO oxidation kinetics, and the water‐gas‐shift reactions in former studies. Aside from the experiments in a stagnation‐flow reactor presented here, we modeled a number of experiments from the literature to test the newly established kinetic scheme.